Precambriam Organic Compounds from the Ketilidian of South-West Greenland, Part I. - Raunsgaard Pedersen, K.; Lam, Jørgen (Meddelelser om Grønland, 1968)
Well preserved Ketilidian sedimentary rocks from South-West Greenland, about 2000 million years old and containing macroscopic and microscopic fossils, have been examined for organic material. The results of the work on the extractions from a coal-graphite layer are presented together with a short description of the local geology around this layer. Straight chain and branched paraffins, mono-, di-, or polycyclic aromatic hydrocarbons, borneol, camphor and other monoterpenoid compounds, fatty acids and methyl esters of fatty acids are present in samples from the coal-graphite layer, together with other organic substances as yet unidentified. Pristane, phytane and other isoprenoid hydrocarbons have been found in small amounts. The presence of these organic compounds indicates a biological origin of the coal-graphite layer. Besides the coal-graphite other sediments (dolomites and quartzites) from the succession have yielded organic material. Further work on these samples and on the coal-graphite is in progress.